Microplastics throughout a tap water supply network - Dalmau‐Soler, Joan; Ballesteros‐Cano, Rubèn; Ferrer, Núria; Boleda, M. Rosa; Lacorte, Sílvia (Water and environment journal : WEJ, 2022)
The aim of the present study was to evaluate the presence of microplastics in drinking water along a large distribution water supply network. Tap water was collected in situ at sampling cabinets using an in‐line sampling procedure that provided a representative sample with minimal risk of external contamination and avoided the transportation of large volumes to the laboratory. Microplastics > 50 μm were analysed via Fourier transform infrared spectroscopy (FTIR). Microplastics were detected in 38% of samples with a mean concentration of 0.01 microplastics per litre and polymers identified were polypropylene (PP), polyester (PES) and polyamide (PA). Detection of polytetrafluoroethylene (PTFE) and silicone particles were associated to the maintenance of cabinets. This study contributes to increase the knowledge regarding the presence and behaviour of microplastics throughout a large drinking water supply network providing water to 3 000 000 inhabitants. Results indicate that the pipes and the supply network not release microplastics into the drinking water.